Ruralidades midiáticas: uma análise sociológica da construção de perfis no Facebook por mulheres do campo - Barbosa, Eduardo (2020)
Country Brazilian residents have been historically portrayed by classical literature and national cinema as inferior to city dwellers, in habits and appearance. The collective imagination is fueled by this creation of another caricature which in turn that is just the result of a hierarchical classification form. This study aims to analyze the ways whereby women from a rural district of a small town, in Brazilian Midwest produce self-narratives on Facebook profiles. The analytical observation of profiles intends to understand how the self-showing in social networks provides alternative narratives to the caricatured model that the collective imagination imprint on country dweller bodies.